2004
DOI: 10.1103/physrevc.69.054308
|View full text |Cite
|
Sign up to set email alerts
|

Shape-changing particle decays ofBi185and structure of the lightest odd-mass Bi isotopes

Abstract: Proton and ␣ decay of the proton-rich nuclide 185 Bi has been restudied in more detail in the complete fusion reaction 93 Nb͑ 95 Mo, 3n͒ 185 Bi at the velocity filter SHIP. The observed decay pattern of 185 Bi and of the heavier odd-mass isotopes 187,189,191,193 Bi are interpreted based on potential-energy surface calculations. It is shown that the experimental systematics of the particle decays and of the excited states in these nuclei (where known) can be explained by the prolate-oblate shape co-existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…It has also been suggested that this ground state coexists with states related to a proton excitation to the i 13/2 orbital or a proton hole in the s 1/2 orbital, giving rise to an oblate deformation (e.g., Ref. [6]). …”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that this ground state coexists with states related to a proton excitation to the i 13/2 orbital or a proton hole in the s 1/2 orbital, giving rise to an oblate deformation (e.g., Ref. [6]). …”
Section: Introductionmentioning
confidence: 99%
“…For the first time we have observed the isomeric intruder 1 [4], and later Andgren et al [32] saw the first γ -ray transitions feeding the 1 /2 + state. In Fig.…”
Section: Discussionmentioning
confidence: 82%
“…If this is the case then the kinematic moment of inertia (1) can be extracted and compared to the kinematic moments of inertia of other cascades in neighboring nuclei. This is shown as a function of rotational frequency ω in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations